The Library Fish Learns to Read - Capucilli, Alyssa Satin, 1957-; Jose, Gladys (New York : Simon & Schuster Books for Young Readers, 2023)
Library Fish, who calls the library her home, decides it is time to learn to do what everyone around her loves doing--read.
Keywords: Fishes -- Juvenile fiction; Libraries -- Juvenile fiction; Books and reading -- Juvenile fiction; Fishes -- Fiction; Libraries -- Fiction; Books and reading -- Fiction; Animal fiction; Picture books